2016
DOI: 10.1186/s12890-016-0289-y
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive versus invasive mechanical ventilation for immunocompromised patients with acute respiratory failure: a systematic review and meta-analysis

Abstract: BackgroundTo determine the effects of noninvasive mechanical ventilation (NIV) compared with invasive mechanical ventilation (IMV) as the initial mechanical ventilation on clinical outcomes when used for treatment of acute respiratory failure (ARF) in immunocompromised patients.MethodsWe searched PubMed, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), the Chinese Biomedical Literature Database (CBM) and other databases. Subgroup analyses by disease severity and causes of immunodeficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 57 publications
(75 reference statements)
0
24
1
Order By: Relevance
“…Previous studies were associated with sustained improvement of reduction in PICU length of stay in patients applied NIV [2,10,[17][18][19]. Although the meaningful relationship was not established in our study, the mean duration of hospitalization was much longer in NIV failure group than that of success group in PICU.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies were associated with sustained improvement of reduction in PICU length of stay in patients applied NIV [2,10,[17][18][19]. Although the meaningful relationship was not established in our study, the mean duration of hospitalization was much longer in NIV failure group than that of success group in PICU.…”
Section: Discussioncontrasting
confidence: 53%
“…However, these meta-analyses included studies focused on immunocompromised, acute cardiogenic pulmonary edema, or post-operative patients; their findings may therefore be less applicable to COVID-19 patients, in whom acute hypoxemic respiratory failure and ARDS are more common presentations. [43,[81][82][83] In acute hypoxemic respiratory failure with an etiology other than cardiogenic pulmonary edema, NIPPV has a high failure rate. In one RCT, failure was reported in 49% of patients with hypoxic respiratory failure ventilated with NIPPV; these patients therefore required intubation [71].…”
Section: Rationalementioning
confidence: 99%
“…Patients who were successfully treated with NIV did not have significantly improved survival in our cohort, however these results were limited by the low numbers in this group. Other observational studies with sufficient numbers have found lower ICU mortality among patients successfully treated with NIV as opposed to IMV, as well as worse survival in those patients who fail NIV . This association of mortality with invasive ventilation, while consistently shown in observational studies, cannot be taken to imply causation given possible confounding by indication which would only be fully accounted for with randomised controlled trial design.…”
Section: Discussionmentioning
confidence: 95%